Quality of life, perceived stress and caregiver burden in mothers of children with childhood psychiatric disorders in Kerala, India - Thomas, Karuna Sandra; Venkateswaran, Chitra; Alexander, Ashwin Varghese (International Journal of Research in Medical Sciences, 2020)
Background: Common childhood psychiatric problems like attention deficit hyperkinetic disorder (ADHD), Pervasive developmental disorder (PDD) and learning disability (LD) often co-exists with each other and form a constellation of behavioural manifestations that require extra attention from the caregivers. Having a differentially-abled child is challenging and most parents have to learn to restructure their lives around that of the child. There is a difference in the attitudes of both the parents as far as parenting a disabled child is concerned. Mothers often shoulder the primary caregiving role however the psychological costs borne by women go unrecognized. The study aims to assess the care giver burden (BOC) and perceived stress (PS) and quality of life (QOL) in mothers of children with ADHD, PDD and LD. Methods: It was a cross-sectional study with 336 child mother pairs. The mothers were asked to rate their burden and stress symptoms on the perceived stress scale and Burden of care scale. The mothers were also asked to rate their quality of life on the quality of life scale. Results: The mean PS score was highest in the PDD group. The mean BOC was lowest in the LD group. The QOL score was highest in the LD group. There is statistically significant difference in the PS, BOC and QOL scores among the three groups. Conclusions: There is a hidden lacuna of psychological stress in mothers of children with common psychiatric problems. The study also establishes that these mothers have poorer quality of life. It is necessary to address these psychological issues of the mother at every visit and equip them with coping strategies so that they can look after both themselves and their special needs child.